An Organocatalytic Process for the Hydrolytic Cleavage of Dithianes Mediated by Imidazolium Ions: No Harsh Agents Required. Issue 1 (26th November 2014) - Myles, Lauren; Gathergood, Nicholas; Connon, Stephen J.
Abstract: A new, organocatalytic approach to the hydrolytic deprotection of dithianes has been developed involving a low‐toxicity imidazolium‐ion‐based catalyst in an aqueous medium. A complimentary solvent‐free method without added water and involving a sacrificial aldehyde is also reported. The catalyst does not appear to operate by a specific‐acid catalysis mechanism. Abstract : A new, organocatalytic approach to the hydrolytic deprotection of dithianes has been developed involving a low‐toxicity imidazolium‐ion‐based catalyst in an aqueous medium.